THE EFFECT OF TAXPAYER AWARENESS, UNDERSTANDING OF TAXES, TAX SERVICES AND TAX SANCTIONS AGAINST COMPLIANCE WITH MOTOR VEHICLE TAXPAYERS IN SAMSAT NGAWI DISTRICT - Eko Meiningsih (ADVANCE, 2019)
This study aims to determine the effect of taxpayer awareness, understanding of taxation, fiscal services and tax sanctions on compliance with motor vehicle taxpayers (PKB) in the Samsat Ngawi District. The population in this study were motor vehicle taxpayers who were registered at the samsat office in Ngawi Regency. The data used are primary data by distributing questionnaires. The method for determining non-probability sampling with Accidental Sampling techniques. Based on Slovin formula obtained a sample of 100 taxpayers. Data analysis method uses validity test, reliability test, classic assumption test, multiple linear regression analysis, hypothesis testing and determination test. The results of hypothesis testing indicate that taxpayer awareness has a positive and significant effect on taxpayer compliance. Understanding of tax has a positive but not significant effect on tax compliance. Fiscal services have a positive and significant effect on tax compliance. Tax sanctions have a positive and significant effect on tax compliance. Adjusted R Square value (R of 58% is influenced by the variables used in 2) is 0.580 or 58%. So R2 of 58% is influenced by the variables used in this study while the remaining 42% is influenced by variables outside the research. For exampletax socialization, income level, samsat corner program, and samsat drive thru system.